Mining Intelligence and Knowledge Exploration Second International Conference, MIKE 2014, Cork, Ireland, December 10-12, 2014. Proceedings - Prasath, Rajendra; O$1 (BReilly, Philip.s; Kathirvalavakumar, T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the Second International Conference on Mining Intelligence and Knowledge Exploration, MIKE 2014, held in Cork, Ireland, in December 2014. The 40 papers presented were carefully reviewed and selected from 69 submissions. The papers cover topics such as information retrieval, feature selection, classification, clustering, image processing, network security, speech processing, machine learning, recommender systems, natural language processing, language, cognition and computation, and business intelligence.
An Effective Term-ranking Function for Query Expansion Based on Information Foraging Assessment -- Using Multi-armed Bandit to Solve Cold-start Problems in Recommender Systems at Telco -- An Improved Collaborative Filtering Model Based on Rough Set -- Learning to Rank for Personalized Fashion Recommender Systems via Implicit Feedback -- Convergence Problem in GMM related Robot Learning from Demonstration: Hybridization of Ensemble Kalman Filter and Non-linear Auto-regressive Neural Network for Financial Forecasting -- Forecast of Traffic Accidents Based on Components Extraction and a Neural Network with Levenberg-Marquardt -- Top-k Parametrized Boost -- Unsupervised Feature Learning for Human Activity Recognition Using Smartphone Sensors -- Influence of Weak Labels for Emotion Recognition of Tweets -- Focused Information Retrieval & English Language Instruction: A New Text Complexity Algorithm for Automatic Text Classification.
Keywords: Computer science; Data mining; Information storage and retrieval; Artificial intelligence; Computer graphics; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books